Media construction of news reports on Malaysia in a Singapore newspaper / Tengku Enaliza binti Tengku Zaman - Tengku Zaman, Tengku Enaliza (2013)
study analyses how language is being used in newspapers to transmit news on Malaysia in a Singapore newspaper, namely The Straits Times, and to express ideologies in order to influence readers' perception towards Malaysia. A sample of articles reporting on events concerning Malaysia in The Straits Times of Singapore are analysed to uncover the representations of Malaysia in the news. The analysis focuses on news reports. Based on Wodak's et al. (1999) framework, it is hoped that this study will uncover the discourse strategies, lexical choices and syntactical structures employed in the news pertaining to Malaysia and to promote Singapore's self-perception on the readers. The analysis revealed that the text producers had employed a variety of strategies to illustrate the events, situations and social actors in the news reports pertaining to Malaysia through lexical choices, syntactical structures and intertextuality for various intended purposes. It was found that the Strategies of Justification and Relativisation; and Strategies of Transformation were used to criticise Malaysia as well as cite Malaysia for various allegations. In describing social actors, the Strategies of Demontage (or Dismantling) and Destruction were used to describe them in an undignified manner by associating them with inappropriate behaviour and equate them with deceitful characters; as well as disclose descriptions that illustrate undesirable situations. Strategies of Perpetuation and Strategies of Transformation were found to be used in depicting outcomes which had adverse effects on situations. Constructive Strategies, on the other hand, were used to impose Singapore’s ‘national self-perception’ by criticising Malaysia. Intertextuality which had negative connotations was also detected in the texts to portray a negative perception on Malaysia. These strategies appear to suggest the ideology of Malaysia as being politically unstable and in chaos, whilst Singapore would be a better country because Singapore is politically stable and safe.